Does obesity’s beliefs matters? Analysis of general practitioners’ speech - Teixeira, Filipa Valente (2011)
Background: The health physicians’ beliefs about obesity have been considered one of the reasons compromising the success of obese people’s treatment. Quantitative research has been criticized for not being able to clarify how health physicians’ practices in the management of obesity are affected by the way they perceived obesity and obese people. Method: Semi-structured interviews about beliefs, attitudes and practices about obesity have been done to Portuguese general practitioners. Data is being analyzed according to Grounded Analysis’ procedures. Expected results: Understanding what physicians think about the causes and consequences of obesity, the adherence behavior of obese and how they perceived their role in the change process. Current stage of work: First interviews were made and analyzed. Discussion: The study of health physicians’ beliefs is an important issue to contribute to the creation of further guidelines to improve their education and practices related to the management of obesity.